2015
DOI: 10.1007/s13277-015-3053-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Trask protein interactions in brain metastatic cohorts of lung cancers

Abstract: A class of adhesion protein that occurs in the membrane with both extracellular and intracellular domain and play vital role in maintaining multicellularity is TRASK, also called CUB-domain containing protein1, CD318 (CDCP1). Specifically, in the current study, documented aggressive grades of lung cancers and distant metastatic tissues were examined for protein interactions of Trask and compared with lung cancer variants in situ. The intracellular domain of Trask has the ability to undergo tyrosine phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…CDCP1, a single-channel transmembrane protein, 4 is overexpressed in NSCLC and is significantly associated with poor prognosis in patients. 5 , 6 , 7 , 8 In malignant tumor cells, CDCP1 can be activated by Src kinase, which promotes the proliferation, invasion, and metastasis of tumor cells through classic signaling pathways such as MAPK (Ras/ERK) and PI3K/AKT. 9 , 10 , 11 , 12 , 13 Besides, numerous studies have demonstrated that antibodies targeting CDCP1, including MAB41-2, MAB10-D7, and C20Fc, can inhibit tumor growth and metastasis in various animal models and improve the efficacy of chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%
“…CDCP1, a single-channel transmembrane protein, 4 is overexpressed in NSCLC and is significantly associated with poor prognosis in patients. 5 , 6 , 7 , 8 In malignant tumor cells, CDCP1 can be activated by Src kinase, which promotes the proliferation, invasion, and metastasis of tumor cells through classic signaling pathways such as MAPK (Ras/ERK) and PI3K/AKT. 9 , 10 , 11 , 12 , 13 Besides, numerous studies have demonstrated that antibodies targeting CDCP1, including MAB41-2, MAB10-D7, and C20Fc, can inhibit tumor growth and metastasis in various animal models and improve the efficacy of chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, measuring activated forms of Akt by in situ PLA does not correlate with phosphorylated Akt or the Akt isoforms as measured by IHC, suggesting that the isoform-specific PLA assays are providing additional clinically relevant information. PLA is showing similar promise for the molecular dissection of a number of other cancers, including lung [78] , [79] , colorectal [80] and prostate [81] cancers. There are fewer publications describing the use of PEA, but this assay has been used to identify five plasma protein biomarkers associated with colorectal cancer, with three of them additionally found to be discriminators of early-stage cancer [55] .…”
Section: Applicationsmentioning
confidence: 99%
“…Macrophages can induce angiogenesis, prepare and modulate stroma proteins in favor of invading tumor cells, thus promoting tumor growth, invasion, and metastasis [58,59] . On the contrary, M1 macrophages might inhibit tumor progression not only in the early phase but also during metastasis formation [60,61] . There are additional pathways by which tumor cells can influence the differentiation of M0-macrophages into M2 lineage.…”
Section: Systems Known To Be Able To Induce Immune Tolerance Towards Foreign Antigensmentioning
confidence: 99%